ChemInform Abstract: Copper Silicides with the Highest Lithium Content: Li7CuSi2 Containing the 16‐Electron Group [CuSi2]7‐ and Li7.3CuSi3 with Heterographene Nets 2∞[CuSi]3.3‐. Issue 9 (5th March 2013) - Slabon, Adam; Budnyk, Serhiy; Cuervo‐Reyes, Eduardo; Woerle, Michael; Mensing, Christian; Nesper, Reinhard
Abstract The new compounds Li7CuSi2 (I) and Li7.3CuSi3 (II) are synthesized from the elements (Nb ampule, 600 °C, 7 d) and characterized by XRD, magnetic measurements, and band structure calculations.